Cytokine Gene Vaccine Therapy for Treatment of a Brain Tumor - Terry Lichtor; Bingtao Tang; Edward J. Roy (Brain Sciences, 2023)
A glioma is a malignant brain tumor with a poor prognosis. Attempts at the surgical removal of the tumor are the first approach, but additional treatment strategies, including radiation therapy and systemic or local chemotherapy, are necessary. Furthermore, the treatments are often associated with significant adverse side effects. Normal and malignant cells generally have antigenic differences, and this is the rationale for clinical immunotherapeutic strategies. Cytokines such as IL-15 or IL-2, which stimulate an anti-tumor immune response, have been shown to have a particularly high potential for use in immunotherapy against various tumors. In this review, treatments with either a poxvirus, genetically engineered to secrete IL-15, or allogeneic fibroblasts, transfected with tumor DNA and engineered to secrete IL-2, are shown to be effective strategies in extending the survival of mice with malignant brain tumors upon intracerebral injection of the treatment cells. Future studies with these treatment strategies in patients with intracerebral tumors are urgently needed.